The drawing-object - Poeiras, Fernando (2022)
This text is the fourth in a series of five in which Fernando Poeiras (ESAD.CR/LIDA), explores the different powers of drawing within architectural design projects. Each text is illustrated with examples from the Drawing Matter Collection.